Effect of Tyrosin Kinase Inhibitors on NK Cell and ILC3 Development and Function - Damele, Laura; Montaldo, Elisa; Moretta, Lorenzo; Vitale, Chiara; Mingari, Maria Cristina (Frontiers in Immunology, 2018)
Tyrosin kinase inhibitors (TKI) sharply improved the prognosis of Chronic Myeloid Leukemia (CML) and of Philadelphia+ Acute Lymphoblastic Leukemia (Ph+ALL) patients. However, TKI are not curative because of the development of resistance and lack of complete molecular remission in the majority of patients. Clinical evidences would support the notion that patient’s immune system may play a key role in preventing relapses. In particular, increased proportions of terminally differentiated CD56+CD16+CD57+ NK cells have been reported to be associated with successful Imatinib therapy discontinuation or with a deep molecular response in Dasatinib-treated patients. In view of the potential role of NK cells in immune-response against CML, it is important to study whether any TKI have an effect on the NK cell development and identify possible molecular mechanism(s) by which continuous exposure to in vitro TKI may influence NK cell development and repertoire. To this end, CD34+ hematopoietic stem cells (HSC) were cultured in the absence or in the presence of Imatinib, Nilotinib, or Dasatinib. We show that all compounds exert an inhibitory effect on CD56+ cell recovery. In addition, Dasatinib sharply skewed the repertoire of CD56+ cell population, leading to an impaired recovery of CD56+CD117-CD16+CD94/NKG2A+EOMES+ mature cytotoxic NK cells, while the recovery of CD56+CD117+CD94/NKG2A-RORγt+ IL-22-producing ILC3 was not affected. This effect appears to involve the Dasatinib–mediated inhibition of Src kinases and, indirectly, of STAT5-signaling activation in CD34+ cells during first days of culture. Our studies, reveal a possible mechanism by which Dasatinib may interfere with the proliferation and maturation of fully competent NK cells, i.e.by targeting signaling pathways required for differentiation and survival of NK cells but not of ILC3.